P PENGARUH KERJASAMA TIM, KOMUNIKASI, LINGKUNGAN DAN KOMPENSASI TERHADAP KINERJA KARYAWN PASCA MERGER BANK SYARIAH INDONESIA - Siti Indah Purwaning Yuwana (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
At the end of 2020, there was a merger between three Sharia Commercial Banks, subsidiaries of BUMN Banks in Indonesia, under the name PT Bank Syariah Indonesia Tbk. The result of the merger was assessed by the Governor of Bank Indonesia to be able to boost the sharia economy and strengthen sharia banking in Indonesia, no exception also applies to the Indonesian Sharia Bank (BSI) Kertosari, Banyuwangi, which is included in the merged bank. This merger can have a positive impact on existing employees, including the company being able to produce higher quality and highly dedicated human resources. This study aims to determine the effect of teamwork, communication, work environment and compensation on employee performance after the merger into Bank Syariah Indonesia. The sample used 17 employees of the Indonesian Sharia Bank (BSI) Kertosari, Banyuwangi. Quantitative analysis of Multiple Linear Regression is used in this study. The results of the study explain that partially teamwork, communication, and work environment have no significant effect on employee performance, while compensation has a significant effect on employee performance. The conclusion can provide important input for the management to remain concerned, or even to increase the compensation given, so that employee performance will increase.